2009
DOI: 10.1021/bm9010672
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Correlation between the Protein Primary Sequences and Secondary Structures in Spider Dragline Silks

Abstract: Synthetic spider silk holds great potential for use in various applications spanning medical uses to ultra lightweight armor, however producing synthetic fibers with mechanical properties comparable to natural spider silk has eluded the scientific community. Natural dragline spider silks are commonly made from proteins that contain highly repetitive amino acid motifs, adopting an array of secondary structures. Before further advances can be made in the production of synthetic fibers based on spider silk protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
140
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(148 citation statements)
references
References 62 publications
8
140
0
Order By: Relevance
“…The GPGXX motif likely forms -turns, and in the case of successive repetition a spiral is formed, as suggested for elastin [27,28]. NMR studies have shown that a fraction of (GA) n and GGX motifs in major ampullate silk are in -sheet as well as less ordered helical structures [23,27]. Table 1.…”
Section: Silk Structurementioning
confidence: 86%
See 1 more Smart Citation
“…The GPGXX motif likely forms -turns, and in the case of successive repetition a spiral is formed, as suggested for elastin [27,28]. NMR studies have shown that a fraction of (GA) n and GGX motifs in major ampullate silk are in -sheet as well as less ordered helical structures [23,27]. Table 1.…”
Section: Silk Structurementioning
confidence: 86%
“…However, only 40% of poly-alanine -sheets in silk fibers are highly ordered while the other 60% exist as poorly aligned -sheet regions [22,23]. The GPGXX and GGX sequences form an amorphous region of protein folds that surrounds the crystalline regions of β-sheets ( Figure 1) [24].…”
Section: Silk Structurementioning
confidence: 99%
“…However, the precise β-sheet content reported varies according to the measurement technique used. Analysis by solid state NMR spectroscopy or Raman microspectroscopy suggests levels of 30 -40%, [29][30][31] as opposed to about 20% identified by XRD. 32 Computer simulations of the crystalline components of silk suggest that the poly-alanine sections align anti-parallel in the H-bonding direction with parallel stacking in the side-chain direction to stabilize the β-sheets.…”
Section: Silk Structure After Spinningmentioning
confidence: 91%
“…In fact, this model first identified the secondary structure composition of the amorphous regions, showing a lack of alpha-helix conformations, but rather a disorderly mixture of structures resembling 3 1 helices and beta-turns, supporting a series of earlier experimental investigations. 26,[28][29][30] Silk's extraordinary properties on the macroscopic scale ultimately stem from the balance of strength and extensibility at the molecular scale. To assess the function of different protein domains, molecular-level deformation mechanisms of the protein composite were examined.…”
Section: Molecular Structure and Mechanics Of Silkmentioning
confidence: 99%